Ultrasound-based bone age assessment in children and adolescents: a mini-review - Zhang, Yixuan; Yang, Xiao; Zhang, Li; Zhao, Zeqing; Yang, Yamei (Frontiers in Pediatrics, 2025)
Bone age assessment is a critical tool for evaluating skeletal maturity in children and adolescents, with implications for growth monitoring and clinical decision-making. While traditional radiographic methods such as the Greulich-Pyle and Tanner-Whitehouse systems remain the gold standard, concerns over ionizing radiation exposure have spurred interest in ultrasound-based alternatives. This mini-review synthesizes current evidence on ultrasound bone age assessment, highlighting its advantages as a radiation-free, non-invasive modality with strong correlations to radiographic standards. Key advancements include standardized scoring systems, ossification ratios (e.g., radius/ulna/femur), and acoustic measures (e.g., speed of sound), which enhance reliability and reduce inter-operator variability. However, challenges persist, including protocol standardization, population-specific variability, and operator dependency, particularly in advanced pubertal stages. Future directions emphasize the development of large-scale, longitudinal and multi-ethnic reference databases, consensus guidelines, and AI integration to improve precision. Ultrasound bone age assessment shows promise as a viable clinical tool, but further refinements are needed to address its limitations and ensure equitable applicability across diverse populations.